2022
DOI: 10.1093/molehr/gaac040
|View full text |Cite
|
Sign up to set email alerts
|

Segmental aneuploid hotspots identified across the genome concordant on reanalysis

Abstract: The aim of this study was to characterize a large set of full segmental aneuploidies identified in trophectoderm (TE) biopsies and evaluate concordance in human blastocysts. Full segmental aneuploid errors were identified in TE biopsies (n=2,766) from preimplantation genetic testing for aneuploid (PGT-A) cycles. Full segmental deletions (n=1,872; 66.1%) presented twice as many times as duplications (n=939; 33.9%), mapped more often to the q-arm (n=1,696; 61.3%), than the p-arm (n=847; 31.0%), or both arms (n=2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This mis-repair leads to DNA damage and segmental errors that may still impact implantation potential, resulting in a higher likelihood of miscarriage and reduced live birth rate if transferred ( Zore et al, 2019 ). Several studies have now shown that segmental aneuploidy is more often mitotic in origin, mostly paternally-derived, and tends to occur within distinct chromosomal regions ( Chavez et al, 2012 ; Babariya et al, 2017 ; McCarty et al, 2022 ; Palmerola et al, 2022 ). Regardless of whether whole and/or partial chromosomes are affected, the DNA will become subjected to further damage due to the fragility of the NE that encapsulates the mis-segregated material, which can have significant consequences for embryo development.…”
Section: Mitotic Mis-segregation Events Often Lead To Chromosomal Mos...mentioning
confidence: 99%
“…This mis-repair leads to DNA damage and segmental errors that may still impact implantation potential, resulting in a higher likelihood of miscarriage and reduced live birth rate if transferred ( Zore et al, 2019 ). Several studies have now shown that segmental aneuploidy is more often mitotic in origin, mostly paternally-derived, and tends to occur within distinct chromosomal regions ( Chavez et al, 2012 ; Babariya et al, 2017 ; McCarty et al, 2022 ; Palmerola et al, 2022 ). Regardless of whether whole and/or partial chromosomes are affected, the DNA will become subjected to further damage due to the fragility of the NE that encapsulates the mis-segregated material, which can have significant consequences for embryo development.…”
Section: Mitotic Mis-segregation Events Often Lead To Chromosomal Mos...mentioning
confidence: 99%